THE IMPACT OF ARTIFICIAL INTELLIGENCE ON ACCOUNTING - Rakhmonova Nilufar (The Conference Hub, 2025)
Artificial Intelligence (AI) is reshaping the traditional practices of accounting by automating routine operations, enhancing analytical capabilities, and supporting strategic decision-making. This paper evaluates the current and potential impacts of AI on accounting, focusing on efficiency, accuracy, and transparency. While AI offers significant advantages in terms of data processing and fraud detection, it also raises challenges related to ethical concerns, data privacy, and the need for professional reskilling. The study highlights the importance of integrating AI responsibly into accounting systems to ensure sustainable growth in the digital economy.
Keywords: Artificial Intelligence, Accounting, Automation, Digital Transformation, Audit, Data Analytics